Achados clínico-patológicos e laboratoriais em um equino com síndrome de Schiff-Sherrington - Câmara, Antônio Carlos Lopes; Braga, Gustavo Peixoto; de Souza, Camila Osse; Moreira, Igor Louzada; Leonardo, André Santos; e Macêdo, Juliana Targino Silva Almeida; Pedroso, Pedro Miguel Ocampos; Fino, Tayná Cardim Morais; Neto, Antonio Raphael Teixeira (Acta Scientiae Veterinariae, 2017)
Background: Schiff-Sherrington syndrome is characterized by extensor hypertonicity of the forelimbs and flaccid hindlimbs as a result from the interruption of the ascending inhibitory effect on motor neurons of forelimbs. The main cause is trauma to the spinal cord in thoracolumbar segment and is considered a common condition in companion animals, but rarely reported in large animals. The present study aimed to report the clinical-pathological and laboratorial findings of a horse with Schiff-Sherington syndrome. Case: A 9-year-old mare weighing 330 kg was referred for clinical evaluation after a 36 h evolution of an acute onset of inability to stand. During physical examination the horse was on lateral recumbency and presented normal mental status, spasticity of the forelimbs, flaccid paralysis of the hind limbs, and superficial sensitivity decreased from the 13th thoracic vertebra, reaching the perianal region and hindlimbs. Hematological and biochemical abnormalities included mild neu- trophilic leukocytosis, hypoalbuminemia and increased activity of aspartate aminotransferase. Cerebrospinal fluid (CSF) analysis showed yellowish coloration (xanthochromia), turbidity (+1), increased density, hypoproteinemia and erythro- phagocytosis. Microbiological culture of CSF was negative. Necropsy revealed muscle hematomas and complete fracture of the 10th and 11th thoracic vertebrae with spinal cord compression. Cross section of the thoracic spinal cord presented severe hemorrhage and cavitations areas in the gray matter. Microscopically, vacuolization of the white matter (status spongiosus) with numerous axonal spheroids was present. In the gray matter, the presence of moderate amount of neurons with eosinophilic cytoplasm, nucleus and retracted picnotic (necrosis), discrete perineuronal edema, and moderate foci of hemorrhage was observed. Discussion: The definitive diagnosis of thoracic vertebral fracture with spinal cord compression and myelomalacia was conducted by the association of epidemiological, clinical, laboratory and pathological findings. Schiff-Sherington syndrome can occur due to serious injuries in the thoracolumbar region with spinal cord compression, resulting in lower motor neuron paralysis in the hind limbs (flaccid paralysis) and upper motor neuron paralysis in the forelimbs (spasticity). In horses, the thoracic segment is the most affected in cases of vertebral fractures. CSF analysis presented as a crucial tool for diagnosis, because it allowed the observation of xanthochromia and erythrophagocytosis. And it also allowed the exclusion of other causes of acute spinal cord impairment, such as rabies, viral myeloencephalitis, protozoal mieloencefalopathy and trypanosomiasis by Trypanosoma evansi. CSF analysis is an important ancillary method, associated with the epidemiological and clinical findings, in the diagnosis of central nervous system diseases in horses. In large animals with suspected fracture and spinal cord compression, CSF analysis can help in the definitive diagnosis, especially when performing radiographic examination is impossible.